Design and pilot testing of an educational strategy based on behavioral and communication models within Mutual Aid Groups to improve the lifestyle of people living with type 2 diabetes in Mexico - Jiménez Aguilar, Alejandra; Georgina Eugenia Bazán-Riverón; Méndez-Gómez-Humarán, Ignacio (Revista Española de Comunicación en Salud, 2025)
Abstract Introduction: Mutual Aid Groups (MAGs) are essential for the self-care of people living with type 2 diabetes (PLD) in Mexico. However, they have areas for improvement, particularly in communication between healthcare providers and PLD. Objective: To design and pilot a Healthy Living Educational Strategy for PLD (HLED) and evaluate its impact on their lifestyle. Methodology: The HLED was implemented in two MAGs (urban and rural) in Cuernavaca, Morelos. It was based on behavioral models and structured on the Multimedia Training Methodology, grounded in the Theoretical Model of Communication for Development and the Participatory Communication Model. The strategy included four monthly theoretical-practical workshops. Pre- and post-tests were conducted using the Validated Instrument to Measure the Lifestyle of PLD, generating a lifestyle index (0–100; higher scores indicate healthier lifestyles). Multiple regression models were used to evaluate the impact. Results: The study included 19 women and 4 men (mean age: 56.2 ± 10 years). Participants attending all workshops scored 34.04 points higher on the lifestyle index compared to those attending only one workshop (95% CI: 20.77, 47.31; p<0.01). Conclusion: The HLED shows potential to improve the lifestyle of PLD in MAGs.